Determination of tropospheric refraction over observation points IRKM (Irkutsk), ULAZ (Ulan-Ude) and BADG (Badary) - M. G. Dembelov; O. F. Lukhneva; A. V. Lukhnev (Геодинамика и тектонофизика, 2018)
The article describes the possibility of using the passive satellite measurements of the atmosphere to investigate the vertical patterns of pressure, temperature and relative humidity and simulate the altitude dependence of the refractive index of air. The seasonal parameters were determined for the exponential model showing the tropospheric refraction over observation points IRKM (Irkutsk), ULAZ (Ulan-Ude) and BADG (Badary). Post-processing of the input GPS data was conducted to ensure the highest positioning accuracy. In addition to high-precision geodesy, the global positioning method was used for determining the total tropospheric zenith delays (ZTD), which values are used to solve the problems of radio physics and meteorology. The angles of refraction and the true distances were estimated and compared in different seasons of the year. This study shows that the angles of refraction at the observation points located in the Baikal zone do not differ significantly in order of magnitude from the values estimated for other climatic zones.